2019
DOI: 10.3390/ma12244226
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Tribological Performance of MAO Coatings by Using a Stable Sol Electrolyte Mixed with Cellulose Additive

Abstract: In this study, micro-arc oxidation (MAO) of aluminum 6061 alloy was carried out within a silicate base electrolyte containing 0.75 g/L of cellulose, and the tribological properties of the coating were investigated. The as-prepared coating was detected by Fourier Transform Infrared Spectroscopy (FTIR), X-ray diffraction (XRD), a scanning electron microscope (SEM) and an energy-dispersive spectrometer (EDS), respectively. The results suggested that cellulose filled in the microcracks and micropores, or it existe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 40 publications
(60 reference statements)
0
5
0
Order By: Relevance
“…The heat rise results in the local melting of elements in electrolytes present between the electrodes, and the solidification of the oxide layer occurs. The silicate-based electrolyte when used by researcher Bosta et al for the PEO process and AC voltage parameters showed the oxide layer thickness up to 18.5 μm with surface roughness up to 1.27 μm [38] with an average surface finish (0.3-0.4 μm). This supports the use of the DC power parameter for the PEO process for a good surface finish which requires less time.…”
Section: Surface Roughness Analysismentioning
confidence: 99%
“…The heat rise results in the local melting of elements in electrolytes present between the electrodes, and the solidification of the oxide layer occurs. The silicate-based electrolyte when used by researcher Bosta et al for the PEO process and AC voltage parameters showed the oxide layer thickness up to 18.5 μm with surface roughness up to 1.27 μm [38] with an average surface finish (0.3-0.4 μm). This supports the use of the DC power parameter for the PEO process for a good surface finish which requires less time.…”
Section: Surface Roughness Analysismentioning
confidence: 99%
“…As shown in Table 2 for the orthogonal test results, the thickness of the ceramic coatings and the surface grinding crack width were regarded as the investigation targets, which were affected by the electrical parameters, such as the electric current, power frequency, duty cycle, and oxidation time. The experimental data and calculation results from the L 8 (2 7 ) orthogonal array design are also given in Table 2. Combined with the range analysis, the interaction effect of the electrical parameters on the coating thickness and grinding crack width were obtained, which are shown in Table 2.…”
Section: Interactive Orthogonal Testmentioning
confidence: 99%
“…Sang Sik Byeon [6] studied the effect of various nitrogen solutions on an oxide coating microstructure. Wei Song [7] investigated the influence of a stable solid electrolyte mixed with a cellulose additive on the tribological performance of micro arc oxidation coatings. In general, micro arc oxidation is conducted in an aqueous electrolyte, however, Alexander Sobolev [8] applied an alternative MAO ceramic coating to a Ti-6Al-4V alloy in molten nitrate salt at a temperature of 280 • C. Not only the electrolyte type, but also the temperature of the electrolyte had a great influence on the coating quality.…”
Section: Introductionmentioning
confidence: 99%
“…It compiles works on vapor-phase deposition processes including atomic-layer deposition (ALD) [ 1 , 2 ], mist-chemical-vapor deposition [ 3 ] and atmospheric-pressure chemical-vapor deposition (APCVD) [ 4 ] methods in which authors have studied the stabilization of metastable phases and the effect of growth conditions on thin film quality, epitaxy, and crystallinity. The Special Issue also includes liquid-phase coatings like sol-gel [ 5 ], solution immersion [ 6 ], micro-arc oxidation [ 7 ], Plasma Electrolytic Oxidation Processing [ 8 ], and single pulse anodization [ 9 ] where the authors were more focused on the coating of aluminum. The last paper reports on a new metal oxide thin film characterization method [ 10 ] that can extract the majority charge carriers’ type, their concentration, and mobility and is extendable to the study of other wide-bandgap semiconductors.…”
mentioning
confidence: 99%
“…In these investigations, the authors mainly investigated how the coating methods could be improved and identified the main parameters that control the growth quality. Song et al studied the tribological performances of micro-arc oxidation of aluminum 6061 alloy with the addition of 0.75 g/L of cellulose into the electrolyte [ 7 ]. They observed an improvement of the coating with a decrease of the roughness along with an increase of cellulose concentration in the electrolyte.…”
mentioning
confidence: 99%